Promotion Of Entrepreneurship Education In Engineering Colleges: A Case Study Of Tirunelveli District - Amirtha Gowri P, Princitta R, (International Journal of Scientific Research and Management (IJSRM), 2015)
Support for entrepreneurship has never been more important than it is now. Education is argued to be an important driver of the decision to start a business. Reinforcing entrepreneurial education in schools, vocational education institutions and universities will have a positive impact on the entrepreneurial dynamism of our economies. Indeed, besides contributing to the creation of social enterprise and business start - ups, entrepreneurship education will make young people more employable and more ‘ intrapreneurial’ in their work within existing organisations, across the social, public and private sectors. Therefore investing in entrepreneurship education is one of the highest return investments in developing countries like India. However, the measurement of its influence is difficult since it is considered to be an endogenous variable. The aim of this paper is to show how entrepreneurship education will empower the entrepreneurship traits of engineering students. The researcher used survey and questioner methods to support her statements and collected the engineering college students’ attitude towards this kind of courses in their degree curriculum. It alarms the need of such education and proposes a challenge to the academic community to take favourable steps in bring this dream into fact.